Effect of Low-Level Laser Therapy (LLLT) in Pulmonary Inflammation in Asthma Induced by House Dust Mite (HDM): Dosimetry Study - Nicole Cristine Rigonato-Oliveira; Auriléia Aparecida de Brito; Luana Beatriz Vitoretti; Gabriel de Cunha Moraes; Tawany Gonçalves; Karine Zanella Herculano; Cintia Estefano Alves; Adriana Lino-; Flávio Aimbire; Rodolfo Paula Vieira; Ana Paula Ligeiro de Oliveira (Hindawi Limited, 2019)
Asthma is characterized by chronic inflammation in the airways. Several models have been proposed for the discovery of new therapies. Low-Level Laser Therapy (LLLT) is relatively new and effective, very low cost, with no side effects. However, there is still no consensus on the optimal dose to be used. In this sense, the objective of the present study was to evaluate the best dose in an experimental model of asthma induced by House Dust Mite (HDM). Balb/c mice received administration of 100 ug/animal HDM and LLLT applications (diode laser: 660 nm, 100 mW and four different energies 1J, 3J, 5J, and 7.5J) for 16 days. After 24 hours, we studied inflammatory, functional, and structural parameters. The results showed that LBI was able to modulate the pulmonary inflammation observed by reducing the number of cells in Bronchoalveolar Lavage Fluid (BALF) as well as reducing the percentage of neutrophils, eosinophils and T lymphocytes. On the other hand, LLLT increased the level of IL-10 and reduced levels of IL-4, IL-5 and IL-13 in BALF. LLLT was able to reduce the production of mucus, peribronchial eosinophils, collagen deposition, bronchoconstriction index, and bronchial and muscular thickening in the airways. We concluded that the use of LLLT in the treatment of chronic inflammation of the airways attenuated the inflammatory process and functional and structural parameters. We emphasize, in general, that the 1J and 3J laser presented better results. Thus, photobiomodulation may be considered a promising tool for the treatment of chronic pulmonary allergic inflammation observed in asthma.